PENGARUH SUHU PENYIMPANAN TERHADAP SIFAT FISIK TABLET EFFERVESCENT EKSTRAK KULIT BUAH NAGA MERAH (Hylocereus polyrhizus) DAN BUAH LEMON (Citrus limon L.) - Zafira, Areta Thea; Muldiyana, Tya; Santoso, Joko (Fakultas Farmasi UMI, 2023)
Effervescent tablet is a dosage form that can produce bubbles originating from an acid and base reaction that forms a gas. The reaction between acids and bases in effervescent tablets is very sensitive to temperature if stored continuously. So that testing for drug stability is very important in evaluating drugs, one of which is by knowing the effect of temperature on drug stability, especially in the form of effervescent tablets. This study aims to determine the effect of storage temperature on the physical properties of effervescent tablets made from red dragon fruit peel extract (Hylocereus polyrhizus) combined with lemon fruit powder (Citrus limon L.). The research method was carried out by storing effervescent tablets at cold temperature (±120C), room temperature (±250C), and warm temperature (±400C). And observed for 1 month with testing every 1 week. The results of this study are storage temperature can affect the physical properties of effervescent tablets made from red dragon fruit peel extract (Hylocereus polyrhizus) with a combination of lemon fruit powder (Citrus limon L.). The best temperature is cold temperature around 120C because at that temperature the acid and base reactions in effervescent tablets are not excessive which results in effervescent tablets still in a stable condition